2010
DOI: 10.1017/s136898000999317x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of protein intake assessed from weighed dietary records against protein estimated from 24 h urine samples in children, adolescents and young adults participating in the Dortmund Nutritional and Longitudinally Designed (DONALD) Study

Abstract: Objective: To date, only a few nutritional assessment methods have been validated against the biomarker of urinary-N excretion for use in children and adolescents. The aim of the present study was to validate protein intake from one day of a weighed dietary record against protein intake estimated from a simultaneously collected 24 h urine sample. Design: Cross-sectional analyses including 439 participants of the Dortmund Nutritional and Longitudinally Designed (DONALD) Study from four age groups (3-4, 7-8, 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 33 publications
4
28
1
3
Order By: Relevance
“…Mädchen Jungen n (gesamt) a n (%) n (gesamt) a n (% ) Geburtskohorte 706 688 Vor 1985 144 (20,4) 142 (20,6) 1985-1992 211 (29,9) 203 (29,5) 1993-1998 124 (17,6) 106 (15,4) 1999-2003 104 ( …”
Section: Tab 1 Charakteristika Der Donald Studienpopulation (Stand 2unclassified
See 2 more Smart Citations
“…Mädchen Jungen n (gesamt) a n (%) n (gesamt) a n (% ) Geburtskohorte 706 688 Vor 1985 144 (20,4) 142 (20,6) 1985-1992 211 (29,9) 203 (29,5) 1993-1998 124 (17,6) 106 (15,4) 1999-2003 104 ( …”
Section: Tab 1 Charakteristika Der Donald Studienpopulation (Stand 2unclassified
“…So wurde die protokollierte Proteinzufuhr mit dem anerkannten Biomarker für Proteinzufuhr, der Stickstoffausscheidung im Urin, verglichen. Dabei zeigte sich eine akzeptable Übereinstimmung der von 439 DONALD Teilnehmern protokollierten Proteinaufnahme mit der aus parallel gesammelten 24-Stunden-Urinen geschätzten Proteinzufuhr [9]. Insgesamt war die Methodenübereinstimmung bei Kleinkindern (Drei-bis Vierjährige) und Schulkindern (Sieben-bis Achtjährige) höher als bei Jugendlichen (Elf-bis 13-Jährige) und jungen Erwachsenen (18-bis 23-Jährige).…”
Section: -Stunden-urinunclassified
See 1 more Smart Citation
“…Overestimation of protein intake by 1?31 g/d was observed in only one study (35) , whereas other studies reported underestimations (18,33,34) . In the majority of cases, validation studies in children, adolescents and adults investigated other nutrients and/or validated nutrient intakes against nutritional assessment tools different from ours (32)(33)(34)(35)(36)(37) . Most of them found an acceptable validity of their tested instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-day weighed dietary records have been shown to have acceptable validity in DONALD participants of various ages (32). They are analyzed using the in-house nutrient database LEBTAB (24), which incorporates information from standard nutrient tables, product labels, or recipe simulation based on the labeled ingredients and nutrients.…”
Section: Dietmentioning
confidence: 99%